Mixed Reality In Architecture, Design And Construction - Wang, Xiangyu.; Schnabel, Marc Aurel. (Springer Netherlands, 2009)
Mixed Reality is moving out of the research-labs into our daily lives. It plays an increasing role in architecture, design and construction. The combination of digital content with reality creates an exciting synergy that sets out to enhance engagement within architectural design and construction. State-of-the-art research projects on theories and applications within Mixed Reality are presented by leading researchers covering topics in architecture, design collaboration, construction and education. They discuss current projects and offer insight into the next wave of Mixed Reality possibilities.